Gender and Peace Education in Afghanistan - Yazdani, Hafiza; Devere, Heather (In Factis Pax: Journal of Peace Education and Social Justice, 2021)
Political instability, war and conflict for long periods and insufficient educational opportunities in this country have exacerbated women’s inequality, and women’s role in contributing to development in Afghanistan has been ignored. However, the current government have ensured that there are greater opportunities for women to have access to education. Advocates of peace education believe that gender equity is important to bring about positive peace. This article reports on a study that examined school textbooks in use in Afghanistan since 2004 and demonstrates that while there is some content that relates to girls and women, it is minimal. It is argued that the textbooks need to be improved if the role of women and their rights are to be recognised.